The Evolution of Sustainable Retailing: A Bibliometric Review (Sustainable Development Insights, 2026)
This study examines the evolution of sustainable retailing through a bibliometric approach to map its intellectual structure, thematic development, and emerging research directions. Using data retrieved from Scopus and analyzed with VOSviewer, the study identifies key publication trends, influential contributors, and dominant research clusters. The findings reveal that sustainable retailing is anchored by core themes such as retailing, sustainable development, and consumption behavior, reflecting a strong integration of sustainability into retail practices and consumer dynamics. Over time, the field has shifted from a primary focus on corporate social responsibility and resource management toward more strategic and performance-oriented perspectives. Additionally, emerging themes such as electronic commerce, carbon emissions, and innovation highlight the growing importance of digital transformation and environmental impact measurement in retail contexts. Despite this progression, several areas—particularly sector-specific applications and operational practices—remain fragmented, indicating opportunities for further research. This study contributes by providing a comprehensive overview of the knowledge structure of sustainable retailing and offers insights for future theoretical and empirical development in this evolving field.
Keywords: Sustainable Retailing; Bibliometric Analysis; Sustainable Development; Consumer Behavior; VOSViewer